Axisymmetric stationary gravitational and Maxwell fields in the general scalar tensor theory - Singh T. (My University, 2025)
It is shown that the axisymmetric stationary gravitational and Maxwell fields in the general scalar tensor theory can be obtained from the axisymmetric stationary Einstein - Maxwell fields. The scalar-tensor analogue of the Kerr-Newman solution has been obtained by this method. © 1984 with the authors.